Pelatihan Penulisan Artikel Ilmiah di Jurnal Nasional bagi Guru SMK N 6 Semarang - Sumarno, Sumarno; Muhtarom, Muhtarom; Hayat, Muhammad Syaiful; Roshayanti, Fenny (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
Many teachers have problems in publishing scientific articles in National Journals. This service activity aims to provide training and assistance for teachers at SMK Negeri 6 Semarang so that they have the knowledge and skills in making scientific articles and can publish them in the National Journal. The method used to achieve this goal is by training more questions and answers and practice as well as mentoring in the publication of scientific articles. The training material is presented with more practice than theory, with a ratio of 25% theory and 75% practice. Community service activities have been able to increase teachers' understanding in preparing scientific articles and submitting scientific articles to the national journal via OJS. This is in line with the results of community service activities where 75% of registered teachers attended training and 85% of trainees scored above 75 based on the results of the training posttest. The increase can be seen from the average pre-test score of 66.13 which increased to 83.60 at the posttest or the equivalent of 87% of participants having understood the preparation of scientific articles.